An educational improvement project to track patient encounters: toward a more complete understanding of third-year medical students' experiences. Issue 4 (3rd August 2009) - Hoffman, K G; Griggs, M D; Kerber, C A; Wakefield, M; Garrett, E; Kersten, C; Hosokawa, M C; Headrick, L A
Abstract : Background: At the University of Missouri School of Medicine (MUSOM), "commitment to improving quality and safety in healthcare" is one of eight key characteristics set as goals for our graduates. As educators, we have modelled our commitment to continuous improvement in the educational experiences through the creation of a method to monitor and analyse patient encounters in the third year of medical school. This educational improvement project allowed course directors to (1) confirm adequate clinical exposure, (2) obtain prompt information on student experiences, (3) adjust individual student rotations to meet requirements and (4) ascertain the range of clinical experiences available to students. Discussion: Data illustrate high levels of use and satisfaction with the educational innovation. We are in our second year using the new Patient Log (PLOG) process and are now considering expanding the use of PLOG into the fourth year of medical school.